CORPORATIONS IN RUSSIAN ECONOMICS OF TODAY - S. A. Shirokovskikh (Модернизация, инновация, развитие, 2016)
In Russian economics there are purely Russian private corporations as well as mixed state/private owned and transnational corporations. Specific ways of forming corporations in Russia resulted in corporate management models different from those used abroad (exclusive of largest holdingcompanies with considerable participation of the state). Difference in the corporation forms is determined by relations between owners and top managers. Efficient and sustainable (in the western sense) functioning of Russian corporations may become effective only after long timeprovided RF ownership right legislation gets simultaneously improved.